Shareholders’ Power in Manage the Company’s Business in Private Limited Company – the Case of Czechia in an International Context - Petr Tomášek (Acta Universitatis Carolinae. Iuridica)
The legal regulation of the Czech limited liability company is distinctive in an international context. While many foreign jurisdictions, to varying degrees, allow shareholders to influence the business management of the company through the general meeting and, for this purpose, to instruct the director (or even decide on a particular matter themselves), Czech company law, as a general rule, explicitly prohibits such a procedure, except where expressly permitted by law. According to established case law, no contrary conclusion may be drawn, even in view of the differing nature of a limited liability company as opposed to a joint-stock company. However, Czech case law and legal doctrine regrettably fail to explore the underlying rationale and objectives of this prohibition in depth. A comparison with the legal framework governing limited liability companies in Germany, Austria, Slovakia, the United Kingdom, Canada, and Australia suggests that shareholders’ intervention in the business management of a limited liability company can be functional, provided that the protection of minority shareholders and creditors remains unaffected and appropriate regard is paid to the director’s liability towards the company. Even these issues, however, can be adequately addressed within the existing framework of Czech legal scholarship.